2020
DOI: 10.1097/md.0000000000022096
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study for the rate of adverse outcomes in unilateral and bilateral abdominal flap breast reconstruction

Abstract: Background: Adverse outcomes after unilateral vs bilateral breast reconstruction involve an unknown level of risk that warrants thorough investigation. Methods: To address this research need, PubMed, Ovid, Medline, EMBASE, and Scopus databases were searched through systematically from January 1, 1990, to January 1, 2019 to retrieve the relevant studies on the risk of postoperative complications after unilateral vs bilateral abdominal flap breast reconstruction. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
3
5
0
Order By: Relevance
“…42,43 The study by Bennett et al 44 in 2018 showed that patients who received bilateral reconstructions were at a greater risk of complications. Conversely, we found that bilateral reconstruction was associated with lower odds of experiencing complications, similar to a prior analysis by Cao et al 45 As bilateral mastectomy and reconstruction gain popularity, it is necessary to continue to investigate ways in which this surgery can be made safer for patients in the perioperative and postoperative periods.…”
Section: Abr Lateralitysupporting
confidence: 83%
“…42,43 The study by Bennett et al 44 in 2018 showed that patients who received bilateral reconstructions were at a greater risk of complications. Conversely, we found that bilateral reconstruction was associated with lower odds of experiencing complications, similar to a prior analysis by Cao et al 45 As bilateral mastectomy and reconstruction gain popularity, it is necessary to continue to investigate ways in which this surgery can be made safer for patients in the perioperative and postoperative periods.…”
Section: Abr Lateralitysupporting
confidence: 83%
“…However, in a meta-analysis of 8122 patients, unilateral reconstruction was associated with a higher risk of flap loss (relative risk, 1.56; P < 0.05). 20 In contrast, Wade et al 18 reported total flap loss was six times greater in bilateral reconstruction (relative risk, 6.4; P = 0.011). Bilateral reconstructions in our cohort were more common in the partial flap loss group (76.5% versus 52.3%; P = 0.081), with a less pronounced difference when comparing total flap loss (66.7% versus 52.7%; P = 0.393).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have been limited by their heterogeneous grouping of reconstruction methods, lack of precise coding of outcomes, and unavailable variables for query. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Informed decisionmaking about breast reconstruction is reportedly low, 23 and more evidence is needed to evaluate the relative risks of comorbidities, body habitus, and cancer-related factors. We performed this institutional analysis to assess risk factors for complications after DIEP breast reconstruction.…”
Section: Ementioning
confidence: 99%
See 1 more Smart Citation
“…It is known from a large meta-analysis that bilateral autologous breast reconstruction yields a higher risk for flap loss than unilateral procedures [10], but interestingly a recent meta-analysis on bilateral DIEP-based breast reconstruction found that the unilateral reconstruction yields an overall higher complication risk for flap complications than cases, including both sides [18]. This fact goes against our findings; however, the authors did also find a higher complication rate concerning the donor site in bilateral cases, which is corresponding to our data [18]. Factors that will have an impact here are not only longer operative time, but also the bigger wound area and higher blood loss, aside from patient factors that have to be considered as well [19].…”
Section: Discussionmentioning
confidence: 99%